Chemotaxonomic studies of 12 Dioscorea species from China by UHPLC‐QTOF‐MS/MS analysis. Issue 2 (31st July 2019) - Li, Xuejiao; Wang, Ying; Sun, Jiachen; Li, Xia; Zhao, Chengcheng; Zhao, Ping; Man, Shuli; Gao, Wenyuan
Abstract: Introduction: Dioscorea species, which contain abundant steroidal saponins, have been used as folk medicines or raw materials to synthesise steroid drugs. Objective: To establish a rapid chemotaxonomic method that will comprehensively resolve confusions about genetic relationships of genus Dioscorea . Methods: A comprehensive strategy using ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry (UHPLC‐QTOF‐MS/MS) was firstly proposed to evaluate the chemotaxonomy of 12 species (27 taxa) from China by hierarchical cluster analysis (HCA) based on the variations of the identified metabolites. Results: Twenty‐eight secondary metabolites (mainly steroidal saponins) were identified. The MS n fragmentation patterns of DA (a new acetylated steroidal saponin at C‐7 position) were firstly reported. Moreover, eight major steroidal saponins were further quantified simultaneously by UPLC‐QTOF‐MS method. According to HCA results, D. bulbifera L. was distinguished with species of sect. Stenophora Uline for pennogenin‐type steroidal saponins. Dioscorea zingiberensis exhibited far distance from other members of sect. Stenophora Uline for two unique saponins. Dioscorea banzhuana may be reclassified into sect. Stenophora . Dioscorea nipponica subsp. rosthornii and D. collettii var. hypoglauca might be separated from their original subspecies/varieties as new species, respectively. Conclusion: The chemotaxonomic method was successfully applied in the study of genetic relationships of Dioscorea species. This study not only enhanced the understanding of chemical constituents, but also laid basic theoretical foundations for the rational utilisation and chemotaxonomy of genus Dioscorea . Abstract : Twenty‐eight secondary metabolites were qualified from Dioscorea plants and eight of them were quantified simultaneously by UHPLC‐QTOF‐MS/MS analysis. Chemotaxonomic method was successfully applied to the study of genetic relationships of 12 Dioscorea species based on the distribution of identified constituents. Chemotaxonomy of 12 Dioscorea species was successfully conducted based on the 28 identified constituents by UHPLC‐QTOF‐MS. 8 major steroidal saponins were quantified simultaneously. The MS fragmentation patterns of DA were firstly reported.